Sensory processing in medically unexplained pain syndrome. A systematic review - Quodling, Nicole; Hoffman, Norman; Carrick, Frederick Robert; Jemni, Monèm (Frontiers in Pain Research, 2025)
Chronic pain is inherently multifactorial, with biological, psychological and social factors contributing to neuropathic pain (NP) and central sensitization (CS) syndromes. Comorbidity between functional disorders and the lack of clinical biomarkers adds to the challenge of diagnosis and treatment, leading to frustration for healthcare professionals and patients. The main objective of this review is to investigate the association between NP, CS syndromes and sensory processing disorders. A structured search was conducted on the PubMed database using the keywords Central Sensitization, Fibromyalgia, Complex Regional Pain Syndrome, and Neuropathic Pain, combined with the keywords Vision, Audition, Olfaction, Touch, Taste, and Proprioception. PubMed was chosen because it is accessible and user-friendly. Articles within the last five years, from 2018 to 2023, have been included. 380 studies on conditions of CS and sensory processing were identified. After applying inclusion and exclusion criteria, the number of retained papers was 78. There were a few emerging themes. Reduced sensory thresholds were found to be comorbid with chronic pain conditions, particularly those with a component of CS. Both cranial nerve and sensory evaluation examinations may prove helpful as potential biomarkers for diagnosis and for potential treatments.